A cooperative strategy of multi-arm coal gangue sorting robot based on immune dynamic workspace. Issue 5 (4th May 2023) - Wang, Peng; Ma, Hongwei; Zhang, Ye; Cao, Xiangang; Wu, Xudong; Qiao, Huanle; Xia, Jing
ABSTRACT: Although the gangue-sorting robot can solve the problems of large particle gangue sorting and green gangue separation, the sorting rate of the robot system is low due to the operation of the robot in a fixed workspace and the unclear mapping relationship between the robot and the task. To address this problem, this paper proposes a collaborative sorting strategy based on an immune dynamic workspace. This paper then constructs the robotic arm gain function based on the change rules and task attribution of the multi-manipulator robot workspace to realize the cooperative operation of multiple robotic arms. It can not only solve the "deadlock" problem in the process of multi-manipulator cooperation, but also improve the sorting efficiency of the robot system. The main contribution of this paper is to solve the problem of low sorting efficiency of multi-manipulator gangue sorting robot, construct a comprehensive gain function of the manipulator, and combine dynamic workspace with immune theory to form an efficient and practical multi-manipulator cooperative control method. Experiments show that the sorting rate of the multi-robot gangue sorting strategy based on immune dynamic workspace is about 20% higher than the traditional method, and the robot system has good stability and reliability.